ANTIOXIDANT ACTIVITIES AND TOTAL PHENOLIC AND FLAVONOID CONTENT VARIATIONS OF LEAF EXTRACTS OF LAURUS NOBILIS L. FROM MOROCCO - Taroq, Amal; El Kamari, Fatima; Aouam, Imane; El Atki, Yassine; Lyoussi, Badiaa; Abdellaoui, Abdelfattah (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study was undertaken to determine antioxidant activity and total phenolic and flavonoid content of ethanol, methanol, ethyl acetate, and aqueous extracts of the leaves of Laurus nobilis L. Methods: Antioxidant properties were measured using three tests: Free radical scavenging activity against 2,2-diphenyl picrylhydrazyl (DPPH), reduction of molybdate, and reducing (Fe3+/Fe2+) power. Total phenolic and flavonoid content was measured by Folin–Ciocalteu and rutin reagent, respectively. Results: The results showed that both the ethanol and water extracts had greater antioxidant activity than ethyl acetate. Aqueous extract exhibited a higher DPPH radical scavenging and reducing molybdate 545.83±5.89 mg equivalent to ascorbic acid/g dry extract. The strong antioxidant activity of water extract was probably due to its high content of phenols. Furthermore, ethanol and water extracts showed higher total flavonoid content with the values: 153.33±3.59 and 127.25±2.60 mg equivalent rutin/g dry extract, respectively. Conclusion: Our results suggested a potent and excellent antioxidant activity of L. nobilis L. extracts of Morocco. Further research has to be done to isolate the pure bioactive compound and could be considered as a potential source of biomolecules for pharmaceutical and food industry.